PERANAN KOMUNIKASI BUDAYA RUNGGU DALAM MENCAPAI RESOLUSI KONFLIK PERCERAIAN SUKU KARO DI DESA BUDAYA LINGGA KECAMATAN SIMPANG EMPAT KABUPATEN KARO: Studi Kualitatif tentang Nilai, Simbol, dan Peran Komunikasi budaya runggu dalam Proses Mediasi penyelesaian konflik secara adat - Sinulingga, Yohana (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study examines the role of runggu cultural communication in resolving divorce conflicts among the Karo tribe in Lingga Cultural Village. The method used is qualitative with a case study approach and in-depth interviews. The runggu forum involves elements of rakut sitelu: kalimbubu, sembuyak, and anak beru. Interpersonal communication in runggu is conducted using polite and focused traditional language. Karo cultural values encourage peaceful resolution and prevent divorce. The mediation and negotiation process is guided by a neutral mediator who understands customs. If the conflict is successfully resolved, a purpursage (peace agreement) is made; if it fails, customary sanctions (purpursage) are imposed. Runggu cultural communication supports conflict resolution based on mutually beneficial win-win solutions. These research findings align with face negotiation theory and intercultural communication. Runggu has proven effective as a conflict resolution mechanism within a collective cultural context.